Low cost high performance self-starting sensorless single phase induction motor drive - Yaser Anagreh; Asma Al-Ibbini (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The present paper is directed to achieve a low-cost high-performance self-starting single phase induction motor (SPIM) drive system. A phase shifted pulse width modulation (PWM) trains feeding the motor will replace the starting and running capacitors. Adaptive sliding mode control, enhance with model reference adaptive control (MRAC), is implemented to achieve high performance sensorless SPIM drive. The obtained results confirm the feasibility of the proposed system in starting and fast tracking the reference speed with nearly zero percentage overshoot and zero steady-state error. Moreover, the proposed SPIM drive system is robust to external load torque disturbances and insensitive to system parameter variations. Extensive simulations have been conducted to confirm the validity of the proposed system.